NEP-TC a rRNA Methyltransferase Involved on Somatic Embryogenesis of Tamarillo (Solanum betaceum Cav.) - Correia, Sandra; Alhinho, Ana T.; Casimiro, Bruno; Miguel, Célia M.; Oliveira, Margarida; Veríssimo, Paula; Canhoto, Jorge (Frontiers in Plant Science, 2019)
Somatic embryogenesis (SE) is an important biotechnological tool for large-scale clonal propagation and for embryogenesis research. Moreover, genetic transformation and cryopreservation procedures in many species rely on efficient SE protocols. We have been studying different aspects related to SE induction and somatic embryo development in tamarillo (Solanum betaceum Cav.), a small tree from the Solanaceae family. Previous proteomic analyses identified a protein (NEP-TC, 26.5 kDa) consistently present in non-embryogenic calluses of tamarillo, but absent in the embryogenic ones. In this work, the role of NEP-TC during SE was assessed by gene expression analysis and immunolocalization. The results obtained demonstrated that NEP-TC is a putative member of the SpoU rRNA methylase family. This protein, present in the cytoplasm and nucleus, is expressed in non-embryogenic cells and not expressed in embryogenic cells. Slightly enhanced SE induction levels in tamarillo plants with NEP-TC down-regulated levels also supports the role of this protein on SE induction. Heterologous expression was used to confirm NEP-TC rRNA methyltransferase activity, with enhanced activity levels when rRNA was used as a substrate. These data relate a putative member of the SpoU methylase family with plant morphogenesis, in particular with SE induction.